Features of educational process organization for surgical dentistry in Conditions of European credit-transfer system introduction for students of dentistry - Burega, Yu. O.; Бурега, Юрій Олексійович; Бурега, Ю. А. (ВДНЗУ "УМСА", 2015)
In connection with introduction of Bolognese training system it is necessary to optimize to contemporary demands the previous surgical dentistry training methods for students of dentistry. The ways of solving this problem are the improvement of student’s motivation during the training process by using the connection between studied discipline and dentist’s practice and development elements of clinical thinking as well as formation in students of Dentistry integral association of knowledge for surgical dentistry with different clinical causes in all patients age categories. For increasing of student’s interest proposed the ability of reception of additional points at the expense of unassisted training and the other kinds of student’s practice. For the improvement of student’s training in conditions of European Credit – Transfer System also proposed to result in correspondence to demands the integration of fundamental discipline with the course of surgical Dentistry that will help to enhance student’s motivation to study discipline. In addition, the fact that the major part of training program is assigned to unassisted studying of material leads to necessary to increase the number of used demonstrative material (dentistry phantoms, electronic atlases, photos, multimedia materials). In the structure of practical classes is necessary to include clinical and situational tasks that are directed not only for realization of current studies’ final control but also can allow students to use received fundamental knowledge in the future practical activity. У зв’язку з впровадженням Болонської системи навчання необхідно оптимізувати існуючу раніше методику викладання хірургічної стоматології для студентів, що навчаються за спеціальністю «стоматологія». Шляхи вирішення цієї проблеми полягають в підвищенні мотивації студентів у процесі навчання через використання зв’язку дисципліни, що вивчається, з практичною діяльністю лікаря-стоматолога, а також формування елементів клінічного мислення, як асоціацію знань з хірургічної стоматології з різноманітними клінічними випадками. Для підвищення зацікавленості студентів пропонується надання можливості отримання з дисципліни за рахунок самостійної учбової роботи та інших видів діяльності студентів. Покращення якості підготовки студентів в умовах Європейської кредитно-модульної системи відповідно до вимог Болонського процесу пропоновано досягти інтеграцією фундаментальних дисциплін з курсом хірургічної стоматології, що допоможе підвищити мотивацію студентів до вивчення предмету. Внаслідок того, що велика частина учбової програми відводиться на самостійне вивчення, виникає необхідність збільшення кількості наочного матеріалу (стоматологічних фантомів, електронних атласів, фотографій, мультимедійного матеріалу). На додаток, у структуру практичних занять необхідно включити клініко-ситуаційні завдання, що направлені не лише на реалізацію підсумкового контролю поточного рівня знань, а також дозволить студентам використовувати отримані базові знання у майбутній практичній діяльності. В связи с внедрением Болонской системы обучения необходимо оптимизировать существующую ранее методику преподавания хирургической стоматологии для студентов, обучающихся по специальности «стоматология». Пути решения этой проблемы заключаются в повышении мотивации студентов в процессе обучения через использование связи изучаемой дисциплины, с практической деятельностью врача-стоматолога, а также формирование элементов клинического мышления, как ассоциации знаний по хирургической стоматологии с различными клиническими случаями. Для повышения заинтересованности студентов предлагается предоставление возможности получения по дисциплине за счет самостоятельной учебной работы и других видов деятельности студентов. Улучшение качества подготовки студентов в условиях Европейской кредитно- модульной системы в соответствии с требованиями Болонского процесса предложено достичь интеграцией фундаментальных дисциплин с курсом хирургической стоматологии, поможет повысить мотивацию студентов к изучению предмета. Вследствие того, что большая часть учебной программы отводится на самостоятельное изучение, возникает необходимость увеличения количества наглядного материала (стоматологических фантомов, электронных атласов, фотографий, мультимедийного материала). В дополнение, в структуру практических занятий необходимо включить клинико-ситуационные задачи, направленные не только на реализацию итогового контроля текущего уровня знаний, а также позволит студентам использовать полученные базовые знания в будущей практической деятельности.
Особливості організації учбового процесу з хірургічної стоматології в умовах впровадження Європейської кредитно-модульної системи для студентів зі спеціальності "Стоматологія"
Особенности организации учебного процесса по хирургической стоматологии в условиях внедрения Европейской кредитно-модульной системы для студентов по специальности "Стоматология"
Keywords: Bologna process; European Credit-Transfer System; surgical dentistry; dentistry; Болонський процес; Європейська кредитно-модульна система; хірургічна стоматологія; стоматологія; Болонский процесс; Европейская кредитно-модульная система; хирургическая стоматология; стоматология